Um entendimento linear sobre a teoria de Peplau e os Princípios da Reforma Psiquiátrica Brasileira Un entendimiento sobre la Teoría de Peplau y los Principios de la Reforma Psiquiátrica Brasileña An agreement about the Peplau's Theory and the principles of the Brazilian Psychiatric Reformation - Taís Veronica Macedo Cardoso; Rosane Mara Pontes de Oliveira; Cristina Maria Douat Loyola (Universidade Federal do Rio de Janeiro, 2006)
Trata de uma análise sobre os conceitos contidos na teoria de Hildegard Peplau, datados de 1952 e associá-los aos preceitos da Reforma Psiquiátrica Brasileira considerando a realidade social e histórica dessa associação. Partiu-se da análise sistemática do livro Interpersonal Relations in Nursing e dos conceitos nele existentes. O estudo foi realizado sob o enfoque da metanálise, que ajudou na compreensão dos conceitos estudados. A partir da análise das duas referências teóricas, compreendemos que os conceitos chaves de Hildegard Peplau ainda hoje são aplicáveis e capazes de orientar com excelência para um cuidado de enfermagem psiquiátrica que atenda aos preceitos organizadores da Reforma Psiquiátrica Brasileira. Trata del análisis de los conceptos contenidos en la teoria de Hildegard Peplau datado de 1952 y de la asociación a los preceptos de la Reforma Psiquiátrica Brasileña considerando la realidad social e histórica de esta asociación. Se partió del análisis sistemático del libro "Interpersonal Relations in Nursing" y de sus conceptos. El estudio fue realizado bajo el enfoque del metanalisis, que nos ayudó a comprender los conceptos estudiados. A partir del análisis de las teorias, comprendemos que los conceptos claves de Hildegard Peplau aún son capaces de orientar com excelencia en los dias actuales un cuidado de enfermería psiquiátrica que atienda a los preceptos organizadores de la Reforma Psiquiátrica Brasileña. The object of study to be developed deals with the concept contained in the theory of psychiatric nursing proposed by Hildegard Peplau and to associate them with the rules of the Brazilian Psychiatric Reformation. Although the beginning was to apprehend the concepts of the theory of psychiatric nursing using the systematic analysis considered in the "Interpersonal Relations". The study was carried through under the approach of metanalise, that in it helped us to understand the studied concepts. From it analyzes of the data, we understand that still, allowing the agreement of the importance of the transformations of this practice, providing an improvement of the helping practice and initiating assistance based on the models of psychosocial rehabilitation.